Common Fixed Point Theorems for a Pair of Self-Mappings in Fuzzy Cone Metric Spaces - Saif Ur Rehman; Yongjin Li; Shamoona Jabeen; Tayyab Mahmood (Abstract and Applied Analysis)
In this paper, we present some common fixed point theorems for a pair of self-mappings in fuzzy cone metric spaces under the generalized fuzzy cone contraction conditions. We extend and improve some recent results given in the literature.